The Gingerbread Man : Usborne First Reading Level 3 - Mairi Mackinnon (London, United Kingdom Usborne Publishing Ltd, 2006)
Everyone wants to catch the Gingerbread Man, but hes just too fast for them. Until he reaches a river, and meets a suspiciously helpful fox. With lively text and enchanting illustrations, this fresh new version of the classic tale is a book to treasure.
Keywords: Leveled Readers